0
$\begingroup$

In my textbook, there is an alternative perspective on the mean value theorem that I don't understand. When we introduced the mean value theorem the first time, the statement looked like this:

https://en.wikipedia.org/wiki/Mean_value_theorem#Formal_statement

Now, the author wants to introduce the mean value theorem in the n-dimensional space, and he begins like this:

The mean value theorem of a function of one variable can be written like this: Assume $f: I \rightarrow \Bbb R$ is differentiable on I $\subset \Bbb R$ and $x, x + \xi \in I$, then there is a $\lambda \in [0, 1]$ such that

$$f(x + \xi) - f(x) = f'(x + \lambda \xi) * \xi$$

He doesn't give a proof on this, and there are a few things that I don't comprehend.

  1. Why is there a $\xi$ on the right side of the equation? (outside of the parenthesis) What does this give me?

  2. What does $f(x + \xi) - f(x)$ tell me? Shall I comprehend this as the slope of the secant that connects $f(x + \xi)$ and $f(x)$?

$\endgroup$
1
$\begingroup$

The quantity $\xi$ can be understood as $\Delta x$ or as $h$ or as $b-a$; for some reason your author likes $\xi$ instead.

The quantity $f(x+\xi)-f(x)$ is the numerator of the slope of the secant line. The slope itself is $\frac{f(x+\xi)-f(x)}{\xi}$.

As said in the other answer, the $\lambda$ outside the parenthesis is a typo for $\xi$. So your equation, with the typo corrected, is equivalent to $$\frac{f(x+\xi)-f(x)}{\xi} = f'(x+\lambda \xi) \quad\text{for some $\lambda \in [0,1]$} $$ You can also, if you like, replace $x$ by $a$ and $x+\xi$ by $b$, to make the notation match what is in the link you provided, but I'll leave that to you.

All that remains is to understand that as $\lambda$ varies from $0$ to $1$, the expression $x+\lambda\xi$ varies between $x$ and $x+\xi$. Thus, the phrase "$f'(x+\lambda\xi)$ for some $\lambda \in [0,1]$" is equivalent to the phrase "$f'(c)$ for some $c$ between $x$ and $x+\xi$".

$\endgroup$
  • $\begingroup$ Thank you very much! But I think you made a little mistake in your answer: You wrote "the expression $x + \lambda \xi$ varies between $x$ to $\xi$", but I guess you actually meant "the expression $x + \lambda \xi$ varies between $x$ to $x + \xi$", didn't you? $\endgroup$ – Julian Jun 23 '16 at 13:49
  • $\begingroup$ Yes, thanks for the correction. $\endgroup$ – Lee Mosher Jun 23 '16 at 13:49
1
$\begingroup$

This is a typo, $\lambda$ should be $\xi$.

As a counter example, take $x=0,\xi=1,f(x)=\sqrt x$. Then

$$f(1)-f(0)=1=\frac1{2\sqrt{\lambda}}\lambda$$ doesn't work, while

$$f(1)-f(0)=1=\frac1{2\sqrt{\lambda}}$$ does.


Update:

$$x\leftrightarrow a,\\x+\xi\leftrightarrow b,\\x+\lambda\xi\leftrightarrow c.$$

$\endgroup$
  • $\begingroup$ Whoops, that was my own mistake, sorry. I edited the question. $\endgroup$ – Julian Jun 23 '16 at 12:39
1
$\begingroup$

What the mean value theorem basically states is that on a continuous function, given two points $(x_1, y_1)$ and $(x_2, y_2)$ where $x_2 > x_1$, the function's derivative somewhere on the interval from $x_1$ to $x_2$ must be equal to the function's average slope $\frac{\Delta y}{\Delta x}$ (or equivalently, $\frac{y_2-y_1}{x_2-x_1}$).

The original equation you gave was $$f(x + \xi) - f(x) = f'(x + \lambda \xi) * \xi$$ which can be rewritten as $$\frac{f(x + \xi) - f(x)}{\xi} = f'(x + \lambda \xi)$$ If we say that $x_1 = x$ and $x_2 = x+\xi$, then the above equation can be rewritten as $$\frac{f(x_2) - f(x_1)}{x_2-x_1}=f'(x+\lambda\xi)$$ Additionally, we can let $x_3 = x+\lambda\xi$. Since $0 < \lambda < 1$, then $x_1 < x_3 < x_2$. Now it is mush easier to see how this mathematical statement is equivalent to the original theorem: $\frac{y_2-y_1}{x_2-x_1} = f'(x_3)$, where $x_3$ is some value between $x_1$ and $x_2$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.